Immersive Technologies as Promotion Tools for Tourism - Apaza-Panca, Cynthia Milagros; Epiquén, Abdías Chávez; Nole, Irma Victoria Martinez; Noriega, Carlomagno Sancho; Agurto Hidalgo, Saraí Lauritzeng; Canova, Jessica Maryurie Viera; Ramos, Erick Joel Hernández; Taboada, Marlon Martín Mogollón; Peña Alvarado, Exilda Elena (Journal of Posthumanism, 2025)
A comprehensive search of Scopus databases was conducted, including articles published between January 2019 and December 2024. To improve the review reports, the guidelines for systematized review report elements were used under the ReSiste-SHC framework, 26 articles met the inclusion criteria and were classified according to the purpose of the study: To address the aspects that cover the use of immersive technologies such as virtual and augmented reality in tourism according to the research of the last 5 years. We were able to identify 7 aspects that play a fundamental role in tourism through immersive technologies, which were enrichment of the tourism experience, promotion, virtual exploration, inclusive tourism, augmented reality (AR) applied to heritage, barriers and challenges, and training for tourism professionals.